My big fat Greek wedding - Wilson, Rita; Hanks, Tom; Goetzman, Gary; Vardalos, Nia; Zwick, Joel; Gold Circle Films; Home Box Office (Firm); MPH Entertainment ([Santa Monica, CA] : Gold Cirlce Films., 2002)
Toula is a quiet, devoted daughter in a big, crazy Greek family. Working in her father's restaurant, she hides behind her family and keeps the world at a distance. One day at the restaurant she finds herself pouring coffee for a man who inspires her to change her life, and the way she sees the world ... forever
Title from container
Director of photography, Jeffrey Jur ; editor, Mia Goldman ; music, Chris Wilson, Alexander Janko ; costume designer, Michael Clancy ; production designer, Gregory Keen.
Cast: Nia Vardalos, John Corbett, Lainie Kazan, Michael Constantine
Cast: Nia Vardalos, John Corbett, Lainie Kazan, Michael Constantine, Gia Carides, Louis Mandylor, Bess Meisler, Andrea Martin, Joey Fantone
DVD format
Keywords: Comedy films; Weddings -- Drama; Man-woman relationships -- Drama; Greek American women -- Drama